2007
DOI: 10.2215/cjn.02960906
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia in Patients with Type 2 Diabetes

Abstract: Hypomagnesemia has been reported to occur at an increased frequency among patients with type 2 diabetes compared with their counterparts without diabetes. Despite numerous reports linking hypomagnesemia to chronic diabetic complications, attention to this issue is poor among clinicians. This article reviews the literature on the metabolism of magnesium, incidence of hypomagnesemia in patients with type 2 diabetes, implicated contributing factors, and associated complications. Hypomagnesemia occurs at an incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
339
4
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 356 publications
(382 citation statements)
references
References 66 publications
15
339
4
6
Order By: Relevance
“…Low serum Mg is a strong independent predisposing factor of IR and T2DM development (39). Therefore, reduced serum Mg level in T2DM may be associated with an increased urinary loss of Mg (9). These results are also consistent with those described in other studies.…”
Section: Original Articleesupporting
confidence: 91%
See 2 more Smart Citations
“…Low serum Mg is a strong independent predisposing factor of IR and T2DM development (39). Therefore, reduced serum Mg level in T2DM may be associated with an increased urinary loss of Mg (9). These results are also consistent with those described in other studies.…”
Section: Original Articleesupporting
confidence: 91%
“…IR in DM can enhance Mg excretion through the kidney. Thus, reduced serum Mg level in T2DM may promote the urinary loss of Mg (9). These results indicated that the reduction of the serum levels of some essential trace metals may be associated with the occurrence of T2DM.…”
Section: Original Articleementioning
confidence: 77%
See 1 more Smart Citation
“…Inverse correlations between magnesium and fasting plasma glucose, HbA1C, HOMA-IR have been observed. 11,12 Factors implicated in hypomagnesemia in diabetics include diets low in magnesium 13 ,osmotic diuresis causing high renal excretion of magnesium, insensitivity to insulin affecting intracellular magnesium transport and thereby causing increased loss of the extracellular magnesium 14 rampant use of loop and thiazides diuretics promoting magnesium wasting, 15,16 diabetic autonomic neuropathies 4 and reduced tubular reabsorption due to insulin resistance 17 . Sometimes the more common use of antibiotics and antifungals such as aminoglycosides and amphotericin in patients with diabetes may also contribute to renal magnesium wasting 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium is the fourth most abundant cation in the human body and the second most abundant intracellular cation 4 . It plays an important role in the carbohydrate metabolism.…”
Section: Introductionmentioning
confidence: 99%